Phosphate binders on iron basis: a new perspective? - Hergesell, Olaf; Ritz, Eberhard (Kidney international, 1999)
Phosphate binders on iron basis: A new perspective? Uremic patients on maintenance hemodialysis are in positive phosphate balance. This is mainly the result of the complex elimination kinetics of phosphate during dialysis. Removal of phosphate is less than net dietary intake. Classical phosphate binders such as calcium carbonate, calcium acetate, and aluminum-based compounds are limited by side effects (hypercalcemia) and outright toxicity (aluminium). There have been numerous recent attempts to develop alternative phosphate binders, e.g., polyallylamine-hydrochloride (Renagel), lanthanum carbonate, and trivalent iron-containing compounds. The latter is based on old observations that iron salts may cause hyperphosphatemia and rickets in experimental animals and in patients. This idea has recently been taken up again, and effective inhibition of net intestinal phosphate uptake in non-uremic and uremic rats has been shown using simple iron salts (citrate, chloride, ammonium citrate) and complex compounds (cross-linked dextran and stabilized polynuclear iron hydroxide). In uremic rats, the latter compound reduces urinary phosphate excretion as an indicator of reduced intestinal phosphate uptake and has also been shown to be effective in subjects with preterminal renal failure. So far, no side effects or short-term toxicity has been observed. The compound appears promising and deserves further evaluation.
Gesehen am 28.10.2021